2002
DOI: 10.1073/pnas.022634999
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysate-pulsed dendritic cells can elicit an effective antitumor immune response during early lymphoid recovery

Abstract: Dendritic cells (DC) can serve to immunize the newborn immune system to foreign antigen. In a lymphopenic environment, naive T cells undergoing homeostasis-driven proliferation can acquire increased sensitivity to antigen stimulation. Here, we evaluated the capacity of DC to effectively prime the host immune system to elicit antitumor effects in the setting of early lymphoid reconstitution after bone marrow transplantation (BMT). Indeed, bone marrowderived, cytokine-driven DC pulsed with whole tumor lysates (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 30 publications
5
111
0
2
Order By: Relevance
“…Considering that, during homeostatic expansion, T cell clonotypes with increased affinity for highly represented ligands have a selective advantage (32)(33)(34) and acquire a preactivated phenotype (9), it is conceivable that homeostatic proliferation is a mechanism that evolved, in part, to allow a rapid resetting of the lymphocyte repertoire for faster and more efficient immune responses. In support of this possibility, we (35) and others (36,37) have shown that homeostatic expansion concurrent with immunization generates T cell populations enriched for CD8 ϩ effectors with enhanced antitumor activities. Here, we report that ␥␦ T cells acquire several activation markers during homeostatic expansion, but whether this principle can be used to more efficiently exploit the anti-tumor potential of these cells remains to be investigated.…”
Section: Discussionmentioning
confidence: 88%
“…Considering that, during homeostatic expansion, T cell clonotypes with increased affinity for highly represented ligands have a selective advantage (32)(33)(34) and acquire a preactivated phenotype (9), it is conceivable that homeostatic proliferation is a mechanism that evolved, in part, to allow a rapid resetting of the lymphocyte repertoire for faster and more efficient immune responses. In support of this possibility, we (35) and others (36,37) have shown that homeostatic expansion concurrent with immunization generates T cell populations enriched for CD8 ϩ effectors with enhanced antitumor activities. Here, we report that ␥␦ T cells acquire several activation markers during homeostatic expansion, but whether this principle can be used to more efficiently exploit the anti-tumor potential of these cells remains to be investigated.…”
Section: Discussionmentioning
confidence: 88%
“…56 In another model, DCs pulsed with breast tumor lysate were more effective at producing a response when administered to lymphopenic mice with a homeostatically expanding T-cell population. 57 The clinical relevance of this phenomenon was recently demonstrated in a randomized clinical trial in which high-dose chemotherapy and autologous stem-cell transplantation caused rapid and effective reconstitution of specific antimicrobial immunity after the early infusion of in vivo primed and in vitro expanded T cells. 58…”
Section: Rationale For Immunodepletionmentioning
confidence: 99%
“…29 Clinical trials of DCs-based vaccines have been applied for cancers such as renal, prostate cancer, lymphoma and melanoma. [30][31][32][33] However, clinical outcomes have been variable. Less than impressive results have been attributed to the often significant dysregulation and impairment of the transferred DCs in the immunosuppressive tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%